PERSEPSI PESERTA DIDIK KELAS VII TERHADAP PEMBELAJARAN DARING PADA MATA PELAJARAN PENDIDIKAN AGAMA HINDU DAN BUDI PEKERTI DI SMP WIDYA SAKTI DENPASAR - Ni Luh Made Anggriantini; Ni Made Anggreni; Ni Nyoman Mariani (Upadhyaya : Jurnal Penelitian Pendidikan, 2023)
Abstract The covid-19 has caused various changes, one of them is the education sector, At first the learning was done face-to-face, now it has turned into online learning. Implementation ofonline learning, especially in Hindu religious and Ethics subjects has already taken by classVII students. However, the perception of this learning is not yet known, therefore it isnecessary to conduct research with the aim of describing the perceptions of class VII studentstowards online learning in the subjects of Hindu Religion and Ethics in Widya SaktiDenpasar Junior High School. This research is a survey research using a quantitativeapproach. The research instrument used was a questionnaire with 34 points of statements.The trial of the research instrument was carried out on 30 students outside the researchsample. The questionnaire is declared valid and reliable (r count = 0.361). Research sampleis the study were class VII students at SMP Widya Sakti Denpasar, totaling 36 respondentswho were determined using the Propotional Random Sampling technique. The data analysistechnique uses descriptive statistics which include frequency attribution dis and histogram.The results showed the perception of class VII students towars online learning on the subjectof Hindu Religion and Ethics Education at the Widya Sakti Junior High School Denpasarin terms of the natural process is good, In terms of physiological processes it is quite good,In terms of psychological it is quite good, and in terms of response or behavior is quite good. Keywords: Student Perceptions, Online Learning, Hindu Religious Education and Ethics